2012
DOI: 10.3171/2011.11.jns11974
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of catheter-associated urinary tract infections among patients in a neurological intensive care unit: a single institution's success

Abstract: This single-center prospective study demonstrated that a comprehensive UTI prevention bundle along with a continuous quality improvement program can significantly reduce the duration of urinary catheterization and rate of catheter-associated UTI in a neuro ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 48 publications
3
73
1
Order By: Relevance
“…This emphasizes the importance of minimizing UTIs, and prior reports in neurosurgical patients have shown that the implementation of a UTI quality improvement program including maintenance of sterility during catheter insertion, product standardization, and early discontinuation can significantly decrease the incidence of UTIs. 63 Although the optimal modality of venous thromboembolism prophylaxis-mechanical alone or in conjunction with pharmacological prophylaxis-remains debated, the strong association between length of hospital stay and both deep venous thrombosis and pulmonary emboli emphasizes the importance of this prophylaxis. Although many of the postoperative complications collected by the NSQIP had the greatest effect size in multivariate regression models evaluating predictors of prolonged hospitalization, it is notable that their addition to models only slightly improved their discriminatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of minimizing UTIs, and prior reports in neurosurgical patients have shown that the implementation of a UTI quality improvement program including maintenance of sterility during catheter insertion, product standardization, and early discontinuation can significantly decrease the incidence of UTIs. 63 Although the optimal modality of venous thromboembolism prophylaxis-mechanical alone or in conjunction with pharmacological prophylaxis-remains debated, the strong association between length of hospital stay and both deep venous thrombosis and pulmonary emboli emphasizes the importance of this prophylaxis. Although many of the postoperative complications collected by the NSQIP had the greatest effect size in multivariate regression models evaluating predictors of prolonged hospitalization, it is notable that their addition to models only slightly improved their discriminatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, 27.4% (26) reported to be performing meatal care once per shift with 5.3% (5) not performing meatal care as shown in Figure 3. Solution used for meatal care 43 (45%) of the respondents reported to be using antiseptic solution, 28% (27) used plain water and 27% (25) used soap and water as shown in Figure 4. …”
Section: Meatal Carementioning
confidence: 99%
“…The drainage bag should be positioned below the level of the bladder to utilize gravity hence facilitating drainage. Correct positioning of the tubing should be by the use of a securement device or tape to facilitate drainage into the bag and prevent reflux of old urine into the bladder as reflux and stagnation contributes to CAUTI [27]. It has been demonstrated that the use of a securement device to prevent movement of the catheter as the patient moves as well as keeping the drainage bag below the level of the bladder are effective in reducing CAUTI rates by 70% [25].…”
Section: Nursing Practice On Utilization and Adherence To Cauti Bundlementioning
confidence: 99%
“…Introducing a UTI bundle (avoidance of catheter insertion, maintenance of sterility, product standardization, early catheter removal) in a single-center neurologic ICU significantly decreased catheter utilization from 100% to 73% and CAUTI from 13.3 to 4.0 per 1,000 catheter-days. 42 7. A CAUTI prevention program including education, implementation of common CAUTI prevention practices, outcomes and process measures, and feedback of CAUTI outcomes and process measures was implemented in pediatric ICUs in 6 developing countries, and a decrease in CAUTI rates from 5.9 to 2.6 per 1,000 catheter-days (relative risk, 0.43 [95% CI, 0.21-1.0]) was reported.…”
Section: Cmentioning
confidence: 99%